Guidelines on use of interventions to enhance healing of chronic foot ulcers in diabetes (IWGDF 2019 update). (16th March 2020) - Rayman, Gerry; Vas, Prashanth; Dhatariya, Ketan; Driver, Vickie; Hartemann, Agnes; Londahl, Magnus; Piaggesi, Alberto; Apelqvist, Jan; Attinger, Chris; Game, Fran
Abstract: The International Working Group on the Diabetic Foot (IWGDF) has published evidence‐based guidelines on the prevention and management of diabetic foot disease since 1999. In conjunction with advice from internal and external reviewers and expert consultants in the field, this update is based on a systematic review of the literature centred on the following: the Population (P), Intervention (I), Comparator (C) and Outcomes (O) framework; the use of the SIGN guideline/Cochrane review system; and the 21 point scoring system advocated by IWGDF/EWMA. This has resulted in 13 recommendations. The recommendation on sharp debridement and the selection of dressings remain unchanged from the last recommendations published in 2016. The recommendation to consider negative pressure wound therapy in post‐surgical wounds and the judicious use of hyperbaric oxygen therapy in certain non‐healing ischaemic ulcers also remains unchanged. Recommendations against the use of growth factors, autologous platelet gels, bioengineered skin products, ozone, topical carbon dioxide, nitric oxide or interventions reporting improvement of ulcer healing through an alteration of the physical environment or through other systemic medical or nutritional means also remain. New recommendations include consideration of the use of sucrose‐octasulfate impregnated dressings in difficult to heal neuro‐ischaemic ulcers and consideration of the use of autologous combined leucocyte, platelet and fibrin patch in ulcers that are difficult to heal, in both cases when used in addition to best standard of care. A further new recommendation is the consideration of topical placental derived products when used in addition to best standard of care.